KAJIAN KEMUNGKINAN PEMBENTUKAN KERJASAMA PERDAGANGAN DAN INVESTASI ASIA TIMUR (DAMPAK PERKEMBANGAN KERJASAMA EKONOMI KAWASAN ASIA TIMUR TERHADAP PERTUMBUHAN EKONOMI INDONESIA) - Umar Fakhrudin; Irma Rahmawati (Buletin Ilmiah Litbang Perdagangan, 2008)
This study to describes how Indonesia can puts its position in the possibility of the formation in the East Asian economic area. Seen from the Gravity Model Analysis and Computed General Equilibrium (CGE), Indonesia could reap bigger profits if this area formed. However this matter also need to give attention to the issues of regionalization of ASEAN as well as other international political issues. Indonesia’s Foreign Direct Investment (FDI) is still low and also needs to be improved in the short term while increasing the international trade flows. Indonesia also needs to takes strategic position in the production network in this region, with attention to the production relation both of forward and backward llinkage, on the production integrated trend line in East Asian which is more strengthened.